A therapeutic option in nutcracker syndrome and ovarian vein insufficiency. (April 2014) - Bekou, V; Zollikofer, C; Nieuwkamp, N; Von Weymarn, A; Duewell, S; Traber, J
Objectives: The nutcracker syndrome (NS) may lead to insufficient perirenal collaterals as well as incompetence of the left ovarian vein with consecutive ovarian vein insufficiency. Methods: A female patient with NS and severe genital varicosis was treated with dilation of the renal vein and coiling of a left perirenal collateral vein feeding an insufficient left ovarian vein (LOV) with pelvic vein varicosity. Results: In re-evaluation 18 month later with left renal vein (LRV) and LOV phlebography, a widely patent LRV was found. The embolized LRV to LOV collateral was occluded. However, left hypogastric phlebography showed incompetent branches of the left hypogastric vein feeding the genital varicose veins. These were successfully embolized with coils and the genital varicosity decreased on follow-up. Conclusions: In our patient a combined therapeutic approach with balloon dilation of the NS and embolization of the genital varicose veins by left hypogastric vein coil was performed.